Operationalizing the Heaven-Earth-Humanity triad: achieving industrial sustainability through land resource efficiency and spatial harmony - Yujia, Zhang; Lihong, Wu; Xinfa, Tang; Guozu, Hao (Frontiers in Environmental Science, 2025)
The current circular economy and triple bottom line (TBL) models exhibit significant limitations in addressing the relationship between industrial production and regions, especially failing to adequately incorporate the cultural-ethical dimension and the dynamic balance mechanism among subsystems, which makes it difficult for them to effectively address key issues such as excessive land consumption, landscape fragmentation, and degradation of ecological carrying capacity. In response to this theoretical gap, this study proposes and empirically tests a more robust and explanatory theoretical “Heaven-Earth-Humanity” (HEH) sustainable industrial governance framework. This framework, by integrating Confucian ethical concepts (operationalized as stewardship, equity, and procedural harmony), emphasizes the synergy among technological flexibility, policy coordination and ecological regeneration, thereby expanding the theoretical and methodological depth of existing industrial ecology research at both theoretical and methodological levels. Through an empirical analysis of 12 pilot regions in China using the Hybrid System Dynamics - data Envelopment analysis model, the research results show that the HEH framework has significantly improved cross-departmental resource efficiency (22%–30%) and reduced carbon intensity (18.2%). Among them, intensive and sustainable land use practices are important paths to achieve this effect. Key contributions of HEH included technological synergy, policy and spatial integration, cycle optimization, and land resource optimization. By embedding Confucian ethics into governance, the framework underscored that industrial resilience hinges on the synergy of technological agility, policy coherence, and ecological regeneration—offering actionable pathways for green industrial transitions.